Banking in the Digital Era: How Social Media is Reshaping Marketing Strategies in the Financial Sector - Alfandi, Safwanuzzaki; Manafe, Leonard Adrie; Andriana, Ririn (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines CIMB Niaga Bank's use of social media for marketing its banking products, focusing on Instagram, Twitter, and Facebook. A qualitative case study approach was used, involving in-depth interviews with five purposively selected respondents, including marketing staff, social media managers, and two customers who engage with the bank’s content. The findings show that while social media has a positive impact on brand recognition, challenges include maintaining consistent content across platforms and measuring the direct impact of social media engagement on account openings or transactions. The study recommends adjusting the tone and format of messages for each platform’s audience and enhancing analytical tools to measure campaign effectiveness. This research paves the way for future studies comparing digital marketing practices in the banking and non-financial sectors in Indonesia.